The region between the M and S genes of porcine haemagglutinating encephalomyelitis virus is highly similar to human coronavirus OC43 - Vieler, Elke; Schlapp, T.; Herbst, W. (Journal of General Virology, 1996)
The nucleotide sequences of the regions between the membrane and spike protein genes of three strains of porcine haemagglutinating encephalomyelitis virus (HEV) were determined. A total of 739 (HEV strain 67N) and 751 (strains NT9 and VW572) nucleotides were sequenced. Two ORFs, potentially encoding proteins of 12.8 and 9.6 kDa, were identified. Pairwise comparisons with the corresponding ORFs in bovine coronavirus (BCV) and human coronavirus (HCV) OC43 revealed sequence similarities of greater than 88.5% at the nucleotide and 85.3% at the amino acid level for the 12.8 kDa ORF product. For the 9.6 kDa ORF product similarities were greater than 96.9% and 95.2%, respectively. An additional 12 nucleotide deletion upstream of the 12.8 kDa ORF start codon was found in HEV 67N compared to NT9 and VW572. These results reveal a genomic organization of HEV in the region analysed that is homologous to HCV OC43 but different from BCV.